Analisis Komunikasi Pemasaran Kopi Chuseyo Dalam Menarik Minat Pembeli (Studi Kasus Di Kopi Chuseyo Cabang Sukasari Kota Tangerang - Rezkyanti, Sarah; Saputra, Faisal Tomi; Khairani, Aulian (Jurnal Ilmiah Wahana Pendidikan, 2024)
Marketing communications assist business people or businesses in providing knowledge to potential customers what kind of product to choose, how to get it, what benefits will get, and all information related to the product or service offered. This research uses descriptive qualitative research. With data collection techniques carried out by means of observation or observation, interviews, and documentation. Data analysis techniques using data reduction, data presentation, data triangulation and conclusions. The results of this study indicate that the marketing communications used are still not optimal in an effort to attract buyers in terms of promotions and participants (buyers). This study uses Kotler's theory, namely the marketing mix with the seven Ps (7P), namely product, price, place, promotion, people, process, and physical evidence. physique). This study concludes that the management of marketing communications for Chuseyo Coffee at the Sukasari branch, Tangerang City in Attracting Buyer Interests, namely by utilizing Instagram social media and through online ordering applications, namely Gofood and Grabfood and the marketing communication barriers for Chuseyo Coffee at Sukasari branch, Tangerang City in Attracting Visitor Interests namely lies in promotions and participants, which is why there is a lack of buyers at Kopi Chuseyo, the Sukasari branch, Tangerang City.